Pengaruh Good Corporate Governance dan Leverage terhadap Kinerja Keuangan (Studi pada Perusahaan Manufaktur yang terdaftar di BEI) - Nita Agustina; kartin aprianti (Universitas Malahayati, 2022)
Purpose of this study to explain how much influence good corporate governance and leverage can affect financial performance. Data was collected bt targeting random sampling from 6 cemen sub-sector companies listed on the Indonesian Stock Exchange between 2016-2020. Multiple linear analysis was used as the analytical method. then tested the hypothesis with a partial T test and simultaneous F test with the determinant coefficient with a significance level of 5%. Management supervision carried out by independent commissioners does not a significant impact on financial performance. Many or at least the number of audit committees in a company does not significant impact on financial performance. low leverage has a significant impact on financial performance. However based on a simultaneous reviews, the combination of independent commissioners, audit committees and leverage has a significant impact on financial performance.